Current and emerging treatment options for vernal keratoconjunctivitis. (3rd April 2017) - Sacchetti, Marta; Bruscolini, Alice; Abicca, Irene; Nebbioso, Marcella; La Cava, Maurizio; Bonini, Stefano; Lambiase, Alessandro
ABSTRACT: Introduction : Vernal keratoconjunctivitis (VKC) is a rare, chronic allergic disease affecting children in prepuberal age. The hallmark of VKC is the presence of conjunctival upper tarsal and/or limbal papillary reaction. Recurrences of inflammation are characterized by intense ocular symptoms of itching, redness and photophobia associated with corneal involvement ranging from punctuate keratitis to corneal shield ulcers with risk of visual impairment. Areas covered : The goals of VKC treatment are to control inflammation, improve quality of life and avoid corneal complications. Topical antiallergic drugs are effective in mild to moderate forms of VKC, while, in the presence of intense symptoms and corneal involvement, short-term, high dose topical steroids are effective in controlling ocular inflammation. However, steroid chronic use leads to severe side effects such as glaucoma and cataract. Topical Cyclosporine A and Tacrolimus showed to be effective as steroid sparing agents, however, they are not yet available in the market for the use in VKC. Expert opinion : Current treatment of VKC is a severity-based approach, however evidence based guidelines are lacking. Novel molecule, targeting pathogenic mechanisms alternative to immune reaction, may improve the management and outcome if this challenging disease.